El Excentrico, 1969-08-05 - Garcia, Humberto:::Publisher:::::::::::: (Garcia Printing; San Jose, California, 2023)
August 5, 1969 [5 de Agosto de 1969]. No Volume or issue number. Cover has a headshot of Bob Mercado, a finance expert and employee of Garcia & Gracia Bail Bonds.